Narodowy system innowacyjny w Polsce i jego elementy - narodowy program foresight - Szostak, Ewa (National Innovation System and Its Elements - National Program Foresight, 2005)
Achievements of temporary science and technology decide not only about competitive position of company, region or country but also about need and scale of intensity and form of restructurization of an economy and what is following about pace of an economic growth.Common research and development policy carried on by the European Union aims mostly to coordinate individual member countries' policies, for instance by setting and realizing of the research programs.The conception of the National Innovation System is an instrument used to analyze domestic innovation's peculiarity in globalization processes. However, the contemporary research on company's innovativeness shows that intensity and signification of interaction and cooperation between particular elements of innovative systems are especially important on the regional level.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 63-74